Secularization, Religious Denominations, and Differences in Regional Characteristics: The State of Research and a Regional Statistical Investigation for Germany - Christian Diller; Philipp Gareis (Religions, 2020)
The paper pursues the question of the relationship between secularization, religious denominations, and regional characteristics. A literature review leads to the formation of six hypotheses. The analysis of regional statistics for Germany shows clear regional differences in the distribution of the denominational affiliation as well as the secularization of the population. Traditional differences between the federal states and their sub-regions are still recognizable. In particular, there is an obvious difference in secularization between the East German and West German states in relation to the significance of the two large Christian denominations. These differences between the paths of regional development and degree of secularization are so large that most of the hypothesis testing on the association between religious affiliation and demographic and socio-economic variables resulted in different findings for the two areas. Further research is required to pursue more regional differentiation and to include non-Christian faiths in the investigations.